2017
DOI: 10.1097/bot.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Implant Choice and Cost in the Treatment of Pediatric Diaphyseal Forearm Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Our results show that intramedullary nailing of upper limb fractures using TEN is more expensive than other fracture stabilization methods. These results are consistent with those of previous studies [15][16][17][18].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results show that intramedullary nailing of upper limb fractures using TEN is more expensive than other fracture stabilization methods. These results are consistent with those of previous studies [15][16][17][18].…”
Section: Discussionsupporting
confidence: 94%
“…This is the standard of care in many hospitals around the world [3,5,19,20]. Furthermore, modifications to the intramedullary nailing technique were introduced by several authors: Some of the authors routinely use a single nail stabilizing both the forearm bones, with comparable results to using the classic two nail insertion technique, or recommend careful consideration when choosing the surgical technique and materials for fracture stabilization [18,23]. On the other hand, when trying to reduce the cost, the entire picture, and not only the cost generated by the inpatient treatment, has to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition to complication rates, the cost to the patient and healthcare system as a whole must be considered when deciding on the optimal treatment of pediatric forearm fractures. 13,16,17 The current study demonstrated a significant amount of baseline variation among orthopaedic surgeons who treat pediatric forearm fractures. With regards to surgeon demographics, there was no statistically significant difference in treatment preferences associated with age, years in practice, and fellowship training among the surgeons that responded to the survey.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, TENs have been shown to cost 26.6 times more than a K-wire per implant. 6 Coupled with the cost of return to theaters, the difference is significant.…”
Section: Expected Outcomesmentioning
confidence: 99%